AFFECTIVE COMMITMENT SEBAGAI VARIABEL MEDIASI ANTARA PENGARUH DISTRIBUTIVE JUSTICE DAN PROCEDURAL JUSTICE TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DI BANK BNI CABANG KEBUMEN - Kharismasyah, Alfato Yusnar (Jurnal Manajemen Bisnis, 2019)
Globalization has had consequences for every organization to implement changes on its internal side. The internal side of the organization includes managing human resources, organizational policy, and situational conditions at the company. Human resources are a driver of creativity and innovation in a company that will increase the reputation and profit of the company in a long period of time. The competition causes banking companies always developing the working system thus providing encouragement for employees both from basic employees to management level to always be active in and have advantages in understanding their job desk. Bank Negara Indonesia (Persero), tbk is one of the Banking Company that always makes changes in both the operational system and human resources to achieve maksimum work result and fair treatment of all employees in accordance with the quality and quantity of their work so that employees feel committed to the organization Organizational citizenship behavior is expected to change the mindset where an employee does not only master an ability to work in accordance with his main task, but also can have the ability to other units outside the job desk. Therefore the purpose of this study is to analyze the effect of distributive justice and procedural justice on OCB through affective commitment.                    This research is descriptive and verification analysis. The method used is the survey method. While the sampling technique is a saturated sample with a total sample of 65 respondents. Data analysis in this research using PLS (Partial Least Square) Analysis. The result show that distributive justice, procedural justice has a significant effect on affective commitments that have an impact on OCB.                    The contribution of this research is to provide advice to managers especially in banking companies to arrange strategies and implement policies related to the management of human resources appropriately And create human resources with all their best abilities to play an extra role in doing their work.